Prognostic Value of "A" Waves in Patients With Guillain Barre Syndrome. Issue 5 (September 2019) - Badry, Reda
Abstract : Introduction: The "A" wave is a compound action potential evoked consistently from a muscle by submaximal electric stimulation to the nerve. "A" waves were usually associated with the presence of conduction block and abounded in lower limbs more than in upper limbs. Guillain Barre syndrome is an autoimmune polyradiculoneuropathy that usually follows respiratory or gastrointestinal infections. Purpose: To study the prognostic value of "A" waves in patients with Guillain Barre syndrome with different recovery patterns. Methods: In this study, 50 patients with GuillainBarreSyndrome were enrolled. They were divided into two groups based on the presence or absence of "A" waves in their neurophysiologic study at onset of illness. Strength of limb muscles of the involved patients was assessed at onset of the study and 6 weeks later (short-term clinical recovery) using the Medical Research Council Scale. Results: Patients with waves (29 patients: 58%) showed poorer short-term follow-up parameters than those without "A" waves (21 patients: 42%). Conclusions: Presence of "A" waves is usually associated with conduction block and marked degree of demyelination. "A" waves carry poor prognostic value in short-term follow-up parameters in patients with Guillain Barre syndrome.